Levrero con Barthes, indagaciones novelescas - Sandra Contreras (Cuadernos LIRICO)
The article exposes the writing experience that Mario Levrero defines as the La Novela Luminosa (The Luminous Novel) realized within twenty years in between interruptions, recoveries and continuations, as a “long-term” novel. With Roland Barthes’ Writing Degree Zero, that in the reading process works as analogon, the aim is to read the Levrero’s parable as a “deliberative route” that investigates in the novel the strength from which the will of writing starts and also the challenges that “the work as will” has to take on. The vital occupation of the “will of writing” involves time and other forms of extension, proceeding between the significance of the original impulse and the impositions of the conclusion.